What Will You Do If I Say 'I Do'?: The Effect of the Sex Ratio on Time Use within Taiwanese Married Couples - Simon Chang; Rachel Connelly; Ping Ma (Institute for the Study of Labor (IZA), 2015)
This paper uses the natural experiment of a large imbalance between men and women of marriageable age in Taiwan in the 1960s to test the hypothesis that higher sex ratios lead to husbands (wives) having a lower (higher) share of couple's time in leisure and higher (lower) share of the couple's total work time (employment, commuting and housework). A large sample of Taiwanese couples' time diaries from 1987, 1990, and 1994 is used. The analysis finds evidence of the predicted effects of the county-level sex ratio on husbands' and wives' share of leisure and total work time. In addition, the age difference between husbands and wives is shown to be positively correlated with heightened county-level sex ratio a result which is also consistent with the theory that marriage market participants' choices are affected by the prevailing sex ratio.
Keywords: J12; J16; 330; sex ratios; time use; time diaries; Taiwan; marriage markets; bargaining power